THE INFLUENCE OF JOB DEMANDS-RESOURCES ON THE QUALITY OF EDUCATION IN RAUDHATUL ATHFAL - Hilma M Shabrina; Hary Priatna Sanusi; Mustaqim Mustaqim (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
The development of early childhood education demands increasingly high quality. The quality of education in Raudhatul Athfal (RA) is strongly influenced by teacher performance, which in turn is influenced by the working environment. This study aims to analyze the influence of Job Demands Resources (JD-R) on the quality of education in RA, Parongpong District. The research method used is quantitative research method. The sampling technique in this study was simple random sampling with a population of 117 RA teachers, and a sample of 54 respondents. The data processing technique used simple linear regression analysis with the help of SPSS. The results of the analysis show that the Job Demands Resources variable has a positive and significant effect on the quality of education. Partially, Job Demands Resources has a contribution of 47% to the quality of education. This finding indicates that the balance between job demands and the availability of work resources is crucial in improving the quality of early childhood education.